2017
DOI: 10.1016/j.paid.2016.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Students, sex, and psychopathy: Borderline and psychopathy personality traits are differently related to women and men's use of sexual coercion, partner poaching, and promiscuity

Abstract: Primary psychopathy traits correlate with sexual coercion, mate poaching, and lack of relationship exclusivity, reflecting instrumental use of others to fulfil personal desires. These sexual behaviors can also be explained by sexual thrill-seeking/impulsivity, or striving for relationship intimacy through fear of abandonment. Given that impulsive thrill-seeking and rejection-avoidance are related to secondary psychopathy and Borderline Personality Disorder, respectively, this study is the first to consider the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Contrary to this, results of Verona, et al [13] showed that BPD-F2 association is strong in both sexes, while BPD-F1 ratio only occurred in men. The study by Khan, et al [22] also observed a similar significant BPD-F2 association for both sexes. These results agree with those of Viljoen, et al [23] who, using classifications of prototypes of the Psychopathic Personality disorder (PPD) and BPD of Comprehensive Assessment of Psychopathic Person- lianism, narcicism and psychopathy and cluster B personality disorders, showing gender differences for all traits and disorders, with men with significantly higher scores in machiavellianism, psychopathy and APD and women in BPD, histrionic disorder of personality and narcissistic personality disorder.…”
Section: Methodsmentioning
confidence: 56%
See 1 more Smart Citation
“…Contrary to this, results of Verona, et al [13] showed that BPD-F2 association is strong in both sexes, while BPD-F1 ratio only occurred in men. The study by Khan, et al [22] also observed a similar significant BPD-F2 association for both sexes. These results agree with those of Viljoen, et al [23] who, using classifications of prototypes of the Psychopathic Personality disorder (PPD) and BPD of Comprehensive Assessment of Psychopathic Person- lianism, narcicism and psychopathy and cluster B personality disorders, showing gender differences for all traits and disorders, with men with significantly higher scores in machiavellianism, psychopathy and APD and women in BPD, histrionic disorder of personality and narcissistic personality disorder.…”
Section: Methodsmentioning
confidence: 56%
“…The selected studies suggest an association between BPD and factor 2 of psychopathy whereas only the study by Khan, et al [22] finds a significant correlation between BPD and factor 1 although to a lesser extent than for F2. These results agree with those observed in the previous literature, where studies such as those of Widiger [10], Miller, et al [11] and Huchzermeier, et al [12] establish a stronger association between BPD and F2 than between BPD and F1.…”
Section: Discussionmentioning
confidence: 93%
“…Items were scored 1 (yes) or 0 (no), with higher scores indicating greater use of sexual coercion. The internal reliability for each subscale has been mixed in previous studies (e.g., Khan, Brewer, Kim, & Centifanti, 2017), which was reflected in this study: nonverbal sexual arousal (α = .81); emotional manipulation and deception (α = .39); exploitation of the intoxicated (α = .38); and the use of physical force or threats (α = .00).…”
Section: Measures Sexual Coercion: Postrefusal Sexual Persistence Scamentioning
confidence: 65%
“…This perspective is consistent with the reported association of female-perpetrated coercion with heightened neuroticism, impulsivity, sexual compulsivity, and insecurity (Carvalho, Rosa & Pereira, 2018;Schatzel-Murphy et al, 2009). Other work has implicated anxious romantic attachment (i.e., increasing attempts for relationship closeness in response to the threat of losing a partner) in women's perpetration of related forms of aggression (ie, intimate partner violence, sexual harassment; Ménard, Shoss & Pincus, 2010;Orcutt, Garcia, & Pickett, 2005), although traits related to insecure attachment (eg, borderline personality disorder) have not consistently demonstrated greater risk for perpetration (Khan, Brewer, Kim, & Centifanti, 2017). In this model, male sexual rejection (a deviation from traditional sexual scripts central to hyperfemininity) may lead to coercion by women as a way of relieving rejection-related distress.…”
Section: Motivations For Sexmentioning
confidence: 99%